A central amygdala to zona incerta projection is required for acquisition and remote recall of conditioned fear memory. (November 2018) - Zhou, Mu; Liu, Zhihui; Melin, Maxwell; Ng, Yi; Xu, Wei; Südhof, Thomas
Abstract The formation and retrieval of conditioned fear memories critically depend on the amygdala. Here we identify an inhibitory projection fromsomatostatin -positive neurons in the central amygdala toparvalbumin -positive neurons in the zona incerta that is required for both recent and remote fear memories. Thus, the amygdala inhibitory input toparvalbumin -positive neurons in the zona incerta, a nucleus not previously implicated in fear memory, is an essential component of the fear memory circuitry. Using genetic tools of neural circuit tracing and manipulation, we identify a novel projection from the amygdala to the zona incerta—a nucleus not previously implicated in fear memory—that is essential for recent and remote fear memories.